Exploring Female Muslim Educational Leadership in a Multicultural Canadian Context - Tasneem Amatullah (Religions, 2024)
This study explores the stories and experiences of female Muslim leaders in K-12 Islamic schools in Greater Toronto Area (GTA), Canada. Using the Islamic Leadership theory and practice framework, visible minority leaders from K-12 Islamic Schools were empowered to share their leadership narratives reflecting on their own identities as females and Muslim leaders in a multicultural context. Based on interviews with five school leaders, this study unveils that female Muslim leaders in K-12 schools prioritize personalized leadership, compassionate treatment of individuals, adaptive leadership, a strong emphasis on faith-based identity, and a theocentric worldview in their practice of educational leadership. Ultimately, this study sheds light on female Muslim educational leaders’ diverse and profound perspectives, showcasing their roles as initiators, role models, and facilitators of positive change in their communities. Their narratives reveal the significance of faith, compassion, and inclusivity in leadership, serving as valuable insights for enhancing leadership practices in Canadian K-12 Islamic education.